Linear and multidirectional speed testing (on-field and off-field) protocols in senior and elite female football - Beato, M.; Datson, N.; Clemente, F. M.; Harper, D. J.; Fílter, A.; Emmonds, S.; Dos' Santos, T.; Jones, P. A. (The Journal of Strength and Conditioning Research, 2025)
Female football has had a considerable rise in popularity with millions of fans after matches during the recent Women's World Cup. Despite this, the football scientific literature is still biased toward male footballers; therefore, this review aims to present the most recent literature and best practices for assessing linear and multidirectional speed and underpinning physical qualities, and to offer practical recommendations based on the most recent evidence and authors' expertise for practitioners working with female football players. This review categorizes tests as on-field and off-field, highlighting common protocols, their advantages, and the existing limitations. Among the most common on-field tests, we found the change of direction speed, horizontal deceleration, linear sprinting, and curved sprinting; although the suggested off-field tests are multi-joint isometric, single-joint isometric, isokinetic dynamometry, Nordic hamstring, and vertical jumps. These tests are valuable tools for assessing players' physical abilities, serving as a benchmark for tracking physical changes throughout the season, and aiding practitioners in individualizing and optimizing training protocols. This review highlights that strength (eccentric, isometric, concentric, and reactive) and rapid force production are crucial for generating braking and propulsive forces, which underpin linear and multidirectional motion. In conclusion, the evidence and practical suggestions reported in this review will improve the practitioners' knowledge of which tests and the consequent training protocols can be used in senior and elite female football players. But practitioners need to be aware about the scarcity of comprehensive studies on female soccer that hinders a complete understanding of the reliability of all assessment protocols used.